Myocardial electroporation — an alternative to thermal methods of atrial fibrillation treatment - E. A. Archakov; R. E. Batalov; M. S. Khlynin; A. V. Smorgon; S. V. Popov (Рациональная фармакотерапия в кардиологии, 2023)
Atrial fibrillation is one of the most common cardiac arrhythmias. By all estimates, the number of patients with this arrhythmia will only increase. Currently, the main and most used methods for the treatment of atrial fibrillation are radiofrequency and cryo-balloon ablation. However, the accumulated experience of their use has revealed a number of shortcomings — the lack of long-term pulmonary vein isolation, as well as life-threatening procedure complications. Relatively recent foreign studies showed data on the use of an alternative method of influencing arrhythmogenic foci. The method is based on the use of non-thermal pulsed field ablation, which leads to the appearance of pores in cardiomyocytes and their necrosis, which causes a more stable electrical left atrial pulmonary vein isolation. The margins of the lesions in this exposure are usually very sharp with a narrow transition from normal tissue to tissue with the complete necrosis, while not damaging neighboring structures such as blood vessels, nerves and esophagus. At present, information published in the literature on the use of pulsed field ablation in various fields of medicine, including oncology and cardiology, is clearly not enough. The implementation of this method for the interventional treatment of cardiac arrhythmias is considered a promising direction and is the subject of research by many leading scientific groups around the world. The purpose of this review is to structure the most significant information on the use of pulsed field ablation, presented in the literature, to analyze its possibilities, effectiveness, and disadvantages.